STUDY OF DIGITAL ARCHITECTURE TECHNOLOGY: THEORY AND DEVELOPMENT - Andadari, Tri Susetyo; Purwanto, LMF; Satwiko, Prasasto; Sanjaya, Ridwan (Journal of Architectural Research and Education, 2021)
Abstract - In the beginning of the 20th century, computerization has developed rapidly affected in all aspects of human life. Computer is not only simplified everything, but it has become an instrument which turned into something that is never thought before. In architecture, digital technology is not only impacted on the architectural planning and design aspects but also on the manufactured finished product. This is the study of literature along with interpretation of the author discussing about the phenomenon of the digital architecture development related to the theory, philosophical study, its evolution and development, as well as a deeper analysis to a few studies on the digital technology especially in the realm of architecture.Â